Scalable Graphene‐on‐Organometal Halide Perovskite Heterostructure Fabricated by Dry Transfer. Issue 1 (3rd December 2018) - Qin, Liang; Kattel, Bhupal; Kafle, Tika R.; Alamri, Mohammed; Gong, Maogang; Panth, Mohan; Hou, Yanbing; Wu, Judy; Chan, Wai‐Lun
Abstract: Graphene, a single layer conductor, can be combined with other functional materials for building efficient optoelectronic devices. However, transferring large‐area graphene onto another material often involves dipping the material into water and other solvents. This process is incompatible with water‐sensitive materials such as organometal halide perovskites. Here, a dry method is used and succeeded, for the first time, in stacking centimeter‐sized graphene directly onto methylammonium lead iodide thin films without exposing the perovskite film to any liquid. Photoemission spectroscopy and nanosecond time‐resolved photoelectrical measurement show that the graphene/perovskite interface does not contain significant amount of contaminants and sustain efficient interfacial electron transfer. The use of this method in fabricating graphene‐on‐perovskite photodetectors is further demonstrated. Besides a better photoresponsivity compared to detectors fabricated by the conventional perovskite‐on‐graphene structure, this dry transfer method provides a scalable pathway to incorporate graphene in multilayer devices based on water‐sensitive materials. Abstract : Centimeter‐sized graphene is transferred onto water‐sensitive organometal halide perovskite using a dry method . The graphene–perovskite interface can sustain effective charge transfer and is potentially used as a building block for fabricating multilayer optoelectronic devices.